Design and Implementation of Web-Based Training Tool for a Single Switch Induction Cooking System Using PHP - Yilmaz, S.; Sazak, B. S.; Cetin, S. (KAUNAS UNIV TECHNOLOGY, 2010)
S. Yilmaz, B. S. Sazak, S. Cetin. Design and Implementation of Web-Based Training Tool for a Single Switch Induction Cooking System Using PHP // Electronics and Electrical Engineering. - Kaunas: Technologija, 2010.- No. 3(99). - P. 89-92. We present a new web-based design method of a single switch resonant inverter (SSRI) for home cooking applications. The tool was implemented using PUP scripts and is freely accessible through Web. Designing a SSRI for induction cooking application is a complex task. Design specifications for the inverter are the input voltage, work coil parameters, water mass and required time for boiling. All other parameters need to be determined. The proposed PHP based design tool will make it faster and easier for the engineer to obtain various design parameters. This design tool employs an intuitive and nonmathematical approach, allowing engineers to rapidly and efficiently learn the fundamentals, instead of wasting too much time on mathematical derivations and algebraic manipulations. A simple design procedure is given and a design example is presented for illustrative purposes. Application is tested local server and published at http://egitimproje.pau.edu.tr/induction/. III. 4, bibl. 11 (in English; summaries in English, Russian and Lithuanian).
Keywords: Engineering